Comparative Microbiota Composition Across Developmental Stages of Natural and Laboratory-Reared Chironomus circumdatus Populations From India - Laviad-Shitrit, Sivan; Sela, Rotem; Sharaby, Yehonatan; Thorat, Leena; Nath, Bimalendu B.; Halpern, Malka (Frontiers in Microbiology, 2021)
Chironomids are aquatic insects that undergo a complete metamorphosis of four life stages. Here we studied, for the first time, the microbiota composition of Chironomus circumdatus, a tropical midge species, both from the Mula and Mutha Rivers in Pune, India and as a laboratory-reared culture. We generated a comparative microbial profile of the eggs, larvae and pupae, the three aquatic life stages of C. circumdatus. Non-metric multidimensional scaling analysis (NMDS) demonstrated that the developmental stage had a more prominent effect on the microbiota composition compared to the sampling location. Notably, the microbiota composition of the egg masses from the different sampling points clustered together and differed from laboratory culture larvae. Proteobacteria was the dominant phylum in all the environmental and laboratory-reared egg masses and pupal samples, while Fusobacteria and Bacteroidetes were the dominant phyla in the larvae collected from the field environment and laboratory cultures, respectively. The most abundant genera were Cetobacterium, Aeromonas, Dysgonomonas, Vibrio, and Flavobacterium while the ten ASVs that most significantly contributed to differences in microbiota composition between the three sampled locations were: Burkholderiaceae, C39 (Rhodocyclaceae), Vibrio, Burkholderiaceae_I, Arcobacter, Bacteroidia, Flavobacterium, Gottschalkia, Bacteroidia_1, and Enterobacteriaceae. No significant differences were found in the microbial richness (Chao1) or diversity (Shannon H') of the three sampled locations. In contrast, significant differences were found between the microbial richness of the three life stages. Studying the microbiota of this Chironomus species may contribute to a better understanding of the association of C. circumdatus and its microbial inhabitants.